1998
DOI: 10.5038/2375-0901.2.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Service Quality Attributes in Public Transport: Inferences from Complaints and Negative Critical Incidents

Abstract: A sample of 200 complaints filed to a public transport company and 210 negative critical incidents (NC!s) obtained from on-board illferviews were analyzed with the purpose of il~ferring perceived service quality (PSQ) attributes of public transport. The most frequent complaints and NC!s concemed employee behavior and punctuality, followed by missing or inaccurate information and inadequate planning. In a follow-up mail survey, a representative sample of 997 respondents reported if they remembered having experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 11 publications
6
31
0
3
Order By: Relevance
“…The ''holistic'' factor is quite the same as the ''efficiency and safety'' dimension found by Thompson and Schofield (2007), and identical to the dimension of simplicity found by Friman et al (1998). This confirms that international tourists prefer to take Taipei's MRT system, which is on time, efficient, and away from heavy traffic.…”
Section: Journal Of Travel and Tourism Marketingsupporting
confidence: 69%
See 1 more Smart Citation
“…The ''holistic'' factor is quite the same as the ''efficiency and safety'' dimension found by Thompson and Schofield (2007), and identical to the dimension of simplicity found by Friman et al (1998). This confirms that international tourists prefer to take Taipei's MRT system, which is on time, efficient, and away from heavy traffic.…”
Section: Journal Of Travel and Tourism Marketingsupporting
confidence: 69%
“…Another study conducted by Thompson and Schofield (2007) identified the salient dimension of public transport performance from the perspective of overseas visitors and found three factors: ''Ease of use,'' ''Efficiency and safety,'' and ''Good parking.'' The ''Ease of use'' factor is closely linked with the dimension of simplicity (Friman, Edvardsson, & Garling, 1998). The factor ''Efficiency and safety'' represents the time and safety dimensions of public transport performance.…”
mentioning
confidence: 99%
“…Based on the work of Friman et al (1998), four incidents were selected that were most typical of HCMC bus service (see Table 1). Respondents were asked about the frequency of negative incidents experienced in the past regarding bus use.…”
Section: Table 1 Attitudinal Factors Toward Bus Service and Negativementioning
confidence: 99%
“…These include trip duration (Ettema et al, 2012; see also Stutzer & Frey, 2008); the activities people perform during a trip ; and the environmental conditions in which travel is undertaken. Unexpected events (delays), cleanliness, safety and social interaction affect satisfaction with public transport trips, while crowdedness and presence of trees/flowers are known to influence satisfaction with walking trips and levels of safety and congestion satisfaction with car trips ; see also Friman et al, 1998Friman et al, , 2001Stradling et al, 2007).…”
Section: Introductionmentioning
confidence: 99%